The Effect of Corporate Risk Disclosure, Company Size, Leverage, And Financial Expertise of The Board of Commissioners On Financial Performance - Dania Ayu Permatasari; Anna Marina; Halimatus Sa’diyah (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This study aimed to determine the effect of corporate risk disclosure, company size, leverage, and the board of commissioners’ financial expertise on financial performance. The corporate risk disclosure variable is measured using a 37-item risk disclosure index. The company size variable calculation used the natural logarithm of total assets. The leverage variable measurement used the total debt-to-equity ratio. The board of commissioners’ financial expertise variable is measured using the proportion of board of commissioners with financial expertise to the total board of commissioners, while the financial performance variable is measured using return on equity (ROE). This research is quantitative, using panel data and analyzed using SPSS 26 software. The sampling technique used was purposive sampling, with mining companies listed on the Indonesia Stock Exchange (IDX) in 2020-2024 as the sample. The sample used in this study was 25 companies. The results of this study indicate that (1) there is a positive and insignificant effect of Financial Corporate Risk Disclosure on Financial Performance. (2) There is a positive and insignificant effect of Company Size on Financial Performance. (3) There is a positive and insignificant effect of Leverage on Financial Performance. (4) There is a positive and significant effect of the Financial Expertise of the Board of Commissioners on Financial Performance. (5) There is a simultaneous effect of Corporate Risk Disclosure, Company Size, Leverage, and Financial Expertise of the Board of Commissioners on Financial Performance.